OVERVIEW OF NEGATIVE EMOTIONAL STATES OF GENERATION Z - Pesau, Heni Gerda (Media Inovasi Pendidikan dan Publikasi, 2025)
Mental health issues are getting important attention nowadays. Mental health problems can be experienced by all ages including generation Z (gen Z). Gen Z is a generation born in 1997-2012. Various problems experienced by Gen Z can trigger feelings of anxiety, depression, and stress or can be called negative emotional states. Gen Z who grew up in an era of rapid technological development, as well as various negative life events are considered vulnerable to experiencing negative emotional conditions. This study aims to analyze the description of the negative emotional conditions of Gen Z through the DASS-21. The research participants were 12-26 years old, male and female, who lived in Makassar. The study used a descriptive quantitative method. The results showed that 36.6% were in the high category, with moderate to severe severity, namely stress at 34.2%, depression at 32.2%, and anxiety at 46.5%. The results of the study indicate the need for intervention that can be started by identifying the causes of negative emotions felt by Gen Z.